Розширення бренда Тараса Шевченка для адвокації українства - Зайченко, Ольга (Київський національний університет імені Тараса Шевченка, 2024)
Стаття є своєрідною присвятою до 210-ї річниці з дня народження Тараса Григоровича Шевченка. Розглянуто в ній факт існування і розвитку особистого бренда Тараса Шевченка за його життя та після смерті, а також можливості його розширення до рівня національного бренда (охоплення нових аудиторій географічно, за межами України, та нових демографічних і соціальних аудиторій в Україні). Для цього серед іншого проаналізовано фотографії Тараса Шевченка 1858–1860 років через призму порад консультантів зі створення особистого бренда, а також використано наявний у відкритих джерелах аналіз шляхів та результатів розширення бренда Тараса Шевченка на терени Галичини ще в часи буття її колонією Австро-Угорщини. Наголошено на можливостях застосування брендингу видатних українців для здійснення адвокації української культури в світі, ребрендингу українства та України, що особливо важливо в умовах війни рф проти України. Звернено увагу на потребу докорінної зміни ставлення країн-лідерів західної цивілізації до «українського питання», до права українства на власну національну державу, остаточного витіснення, елімінування московського наративу про бездержавність українства, про синонімічність Русі та росії тощо зі свідомості політичних еліт цих країн. Зазначено, що війна, яка точиться на теренах України, має світовий та світоглядний характер і бере свій початок ще від так званої «весни народів», та наголошено у зв’язку з цим на потребі змінити наратив, який транслює Україна в світі – акцентувати місійність українства як споконвічного захисника та популяризатора цінностей західної цивілізації, зокрема на прикладі життя і творчості Тараса Шевченка, найвідомішого українця, який давно перетворився на національний бренд для самих українців. Зосереджено увагу на можливості застосування акціонізму та участі креативних індустрій у брендингу Тараса Григоровича та адвокації українства в світі, аналізуючи при цьому наявні практики українських митців та дієвців культури.

The article is a kind of dedication to the 210th anniversary of Taras Hryhorovych Shevchenko's birth. The author examines the existence and development of Taras Shevchenko's personal brand, during his life and after his death, as well as the possibility of its expansion to the level of a national brand (covering new audiences geographically, outside of Ukraine and new demographic and social audiences in Ukraine as well). For this purpose, among other things, the author analyses Taras Shevchenko’s photographs from 1858–1860 through the prism of the advice of consultants on creating a personal brand, as well as applies the available in open-source analysis of the ways and results of the expansion of Taras Shevchenko's brand on Galicia territory back in the days when it had been an Austro-Hungarian colony. The next emphasis of this article is on the possibilities of establishing the branding of prominent Ukrainians for the advocacy of Ukrainian culture in the world, the rebranding of Ukrainianness and Ukraine, which is especially important in the conditions of the russian federation's war against Ukraine. The author also draws attention to the need for radical changes in the attitude of the leading countries of Western civilization towards the "Ukrainian issue," to the right of Ukrainians for their own national state, the final displacement, and the elimination of the moscow narrative about the statelessness of Ukrainians, as well as the synonymy of Russia and Rus', etc., from the minds of the political elites of these countries. Autor states that the current war, although it is taking place on the territory of Ukraine, has a global and worldview character, dates back to the so-called "Spring of Nations," and emphasizes, in this regard, the need for the next change in Ukrainian narrative broadcasted around the world - to emphasise the mission of the Ukrainian nation as a traditional defender and popularizer of Western civilization values, in particular on the example of the life and work of Taras Shevchenko, the most famous Ukrainian, who has long been turned into a national brand for Ukrainians themselves. Another emphasis of this article is on the possibilities of applying actionism and the participation of creative industries in the branding of Taras Hryhorovych and Ukraine's advocacy around the world while analysing the existing practices of Ukrainian artists and cultural workers.
Extension of the Taras Shevchenko brand for the advocacy of the ukrainian nation
Keywords: адвокація інтересів України; бренд нації; особистий бренд; розширення бренда; актуалізація бренда; акціонізм; зміна українського наративу; світоглядна війна; advocacy of Ukraine's interests; brand of the nation; personal brand; brand extension; brand actualization; actionism; change of Ukrainian narrative; worldview war